2022
DOI: 10.1002/slct.202200943
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on Modification and Application of Raw Lacquer

Abstract: Raw lacquer is a kind of natural polymer coating with excellent performance. The lacquer film formed after drying of pure natural raw lacquer has the advantages of hard quality, heat resistance and corrosion resistance. However, natural raw lacquer also has some disadvantages. For example, it must be dried at a specific temperature and humidity to form a film, difficult to spray, dark color, poor alkali resistance, easy to cause human skin allergy and so on. Due to urushiol is the main film‐forming material in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…In line with these results, many scientists have carried out research on the preparation and structure regulation of polymer membrane materials according to the DA self-polymerization-composite method, and have achieved remarkable results. For instance, because of its high specific surface area and excellent permeability, titanium carbide (MXene) membrane has outstanding performance in solvent nanofiltration, but the property of removing pollutants needs to be improved [ 54 ]. Based on this problem, Feng et al.…”
Section: Application In Adsorption Materialsmentioning
confidence: 99%
“…In line with these results, many scientists have carried out research on the preparation and structure regulation of polymer membrane materials according to the DA self-polymerization-composite method, and have achieved remarkable results. For instance, because of its high specific surface area and excellent permeability, titanium carbide (MXene) membrane has outstanding performance in solvent nanofiltration, but the property of removing pollutants needs to be improved [ 54 ]. Based on this problem, Feng et al.…”
Section: Application In Adsorption Materialsmentioning
confidence: 99%
“…With the deepening of the study of raw paint, more properties of raw paint have been further revealed. For example, raw paint has excellent heat resistance and insulation, dark color, high gloss and hardness and good chemical resistance and corrosion resistance [6,7]. Modified raw lacquer can be used in many fields, such as ships, decoration and protection, high-grade wood furniture and textiles and inner walls of oil pipelines in the petroleum industry [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] Many polymer materials with excellent performance (such as efficient energy conversion, higher sensory sensitivities, stable, and degradable) have appeared, 31,32 among which lacquer phenol formaldehyde resin and epoxy resin modied oriental lacquer are the most representative. 33,34 Therefore, based on the principle of modied oriental lacquer and the characteristics of prepolymer in ink (such as high dispersion, low viscosity, low pollution, and environmental protection). A new lm-forming resin with excellent properties of oriental lacquer can be synthesized as a component for the preparation of painting oriental lacquer ink.…”
Section: Introductionmentioning
confidence: 99%